Evaluation of a prototype for a reference platelet counter. - Lewis, S M (1990)
A semiautomated single channel aperture-impedance particle counter was developed as a prototype for a reference platelet count for assigning values to reference preparations used in automated blood cell counts. The instrument is equipped with sheath flow and an aperture orifice of 50 microns in diameter and 60 microns in length to eliminate non-axial flow and minimise coincidence errors. Use of fixed volume and red blood cell:platelet ratios obviate dilution errors. The counter was assessed in accordance with the International Committee for Standardization in Haematology protocol for evaluation of automated blood cell counters. The counter provided a high level of linearity and precision, accurate coincidence correction, controlled volume, stability and negligible carryover.